Toxicological effect of engineered nanomaterials on the liver. (2nd July 2014) - Kermanizadeh, A; Gaiser, B K; Johnston, H; Brown, D M; Stone, V
<x xml:space="preserve">Abstract</x> The liver has a crucial role in metabolic homeostasis, as it is responsible for the storage, synthesis, metabolism and redistribution of carbohydrates, fats and vitamins, and numerous essential proteins. It is also the principal detoxification centre of the body, removing xenobiotics and waste products by metabolism or biliary excretion. An increasing number of studies have shown that some nanomaterials (NMs) are capable of distributing from the site of exposure (e.g. lungs, gut) to a number of secondary organs, including the liver. As a secondary exposure site the liver has been shown to preferentially accumulate NMs (>90% of translocated NMs compared with other organs), and alongside the kidneys may be responsible for the clearance of NMs from the blood. Research into the toxicity posed by NMs to the liver is expanding due to the realization that NMs accumulate in this organ following exposure via a variety of routes (e.g. ingestion, injection and inhalation). Thus it is critical to consider what advances have been made in the investigation of NM hepatotoxicity, as well as appraising the quality of the information available and gaps in the knowledge that still exist. The overall aim of this review is to outline what data are available in the literature for the toxicity elicited by NMs to the liver in order to establish a weight of evidence approach (for risk assessors) to inform on the potential hazards posed by NMs to the liver. Linked Articles This article is part of a themed section on Nanomedicine. To view the other articles in this section visit http://dx.doi.org/10.1111/bph.2014.171.issue‐17